Dialektika Pesantren Dan Radikalisme Di Pesisir Utara Lamongan - Mujib Ridlwan (IAI Darussalam, 2019)
This article wants to explain about the dialectics of pesantren and radicalism by taking place in the region of Lamongan Regency. The National Counter-Terrorism Agency (BNPT) had announced that there were dozens of pesantren from thousands of pesantren in Indonesia indicated to be involved in recruiting radical santri, including one in Lamongan. But the announcement of the BNPT caused an assessment to be generalized towards all pesantren in Indonesia by foreign observers, that all (not some) pesantren in Indonesia teach radicalism. Evil acts committed by a handful of people cause many other people to be affected. In fact, pesantren which are accused of being indicated to teach radicals also deny that they teach radicals. What exactly is the pesantren dialectic and radicalism and what kind of pesantren teach radicalism? The results of interviews and field findings can prove whether there really is pesantren dialectic and radicalism.